Forest certification in Malaysia: current status and challenges - Mohamed, Shukri; Yaakob, Sam Shor Nahar (Forestry Department Peninsular Malaysia, 2015)
Forest certification has two purposes, firstly to certify standards of forest management (forest management certification), and secondly, to certify that timber products are made from wood sourced from the certified forests (chain-of-custody (CoC) certification). Forest certification in Malaysia started with the implementation of the Malaysian Timber Certification Scheme (MTCS) in 2001. This paper highlights the current status of the Malaysian forest industry’s participation in forest certification and trade of certified timber products. To date, about 5.39 million ha of forests in Malaysia are certified. The largest area is Pahang FMU (1,524,827 ha), followed by Perak FMU (991,436 ha) and Sabah (557,452 ha). As of 2015, slightly more than 500 firms are CoC certificate holders, thus participation in CoC certification is considered low as this number is much lower than the number of forest product manufacturers and traders in the country. The European market has been the major export destination for MTCS-certified timber products, and more recently other markets including the Middle East, USA, Australia, New Zealand, India and South Africa have accepted these timber products. Even though export of these timber products is increasing, their share in Malaysia’s timber products export is not significant. The greatest challenge is to increase market acceptance of MTCC’s certification scheme and thus expanding the market for MTCS-certified timber products.